Effect of Electroacupuncture on Reperfusion Ventricular Arrhythmia in Rat - 曾青 李熳 欧阳兴飚 农艺 刘晓春 施静 关新民 (Journal of Huazhong University of Science and Technology. Medical sciences, 2006)
Protective effect and mechanism of electroacupuncture （EA） on acute reperfusion ventricular arrhthmia was investigated. Ventricular arrhythmia was induced by occlusion of the proximal left anterior descend （LAD） branch of coronary artery for 5 min and followed with 15 min reperfusion . EA on acupoint ＂Neiguan＂, ＂Jianshi＂ was performed at 30 min before ligation and continued another 5 min during ischemia. Isoprenaline （20, 30 and 50 μg/kg） or atropine （1 mg/ kg） was intravenously injected at 5min before ischemia. The results showed that EA significantly decreased the incidence of ischemia/reperfusion （I/R） induced ventricular tachycardia （VT）, ventricular fibrillation （VF） and mortality as compared to I/R group. Atropine partially suppressed the EA＇s effect of antiarrhythmia; Isoprenaline increased the incidence and severity of reperfusion arrhythmia, which was inhibited by EA, but this inhibition of EA was blocked with increasing dose of isoprenaline. The results indicated that EA treatment could prevent the occurrence of reperfusion ventricular arrhythmia in rats with myocardial ischemia, and its mechanism might be related to the regulation of EA on the β-adrenoceptors and M-cholinergic receptor activation in myocardium.